MATHEMATICAL MODELING OF GLUCOSE YIELD FROM CASSAVA STARCH VIA ENZYMATIC HYDROLYSIS: A MICHAELIS-MENTEN KINETIC APPROACH - Ismail, Santali; Galadima, James Ibrahim; Abdulkadir, Abubakar; Yakubu, Aisha Aliyu (FUDMA JOURNAL OF SCIENCES, 2025)
Enzymatic hydrolysis of cassava starch into glucose is a critical process in biofuel and food industries, yet its efficiency is influenced by complex kinetic interactions. This study develops a mathematical model based on Michaelis-Menten kinetics to predict glucose yield, incorporating substrate inhibition, product inhibition, and dynamic substrate depletion. By analyzing the effects of enzyme concentration, initial starch concentration, and reaction time, the model provides a mechanistic understanding of the hydrolysis process. Experimental validation confirms the model’s accuracy in simulating real-world conditions. The results demonstrate optimal parameter ranges for maximizing glucose production, offering valuable insights for industrial-scale process optimization. This work bridges theoretical enzyme kinetics with practical applications, enhancing the sustainable utilization of cassava starch as a renewable feedstock.